Translation and cultural adaptation of the Perceived Stigmatization Questionnaire for burn victims in Brazil - Noélle de Oliveira Freitas; Marina Paes Caltran; Rosana Aparecida Spadoti Dantas; Lidia Aparecida Rossi (SciELO, 2014)
This methodological study aimed to describe the process of translation and cultural adaptation of the Perceived stigmatization Questionnaire (PSQ) and analyze the internal consistency of the items in the step of pre-testing. The PSQ was developed to evaluate the perception of stigmatizing behaviors of burn victims. The adaptation process was carried out from August 2012 to February 2013, comprising the steps outlined in the literature. As part of this process, the pre-test with 30 adult burn victims was held. All participants at this step reported to understand the instrument items and the scale of responses. There were no suggestions or changes in the tested version. The value of Cronbach's alpha at pre-test was 0.87. The contribution of this study is to describe the operation of each of the steps of this methodological process and show the internal consistency of the items in the pre-test.